2018
DOI: 10.3389/fmed.2018.00223
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Urogenital Schistosomiasis-Related Bladder Cancer: An Update

Abstract: Infection with Schistosoma haematobium leads to urogenital schistosomiasis, which has been correlated with the occurrence of bladder cancer. However, mechanisms responsible for this association have not yet been clearly identified. In this short review, we provide an update, highlighting the most recent studies on schistosome-associated bladder cancer, including those that focus on identifying changes in host biology during S. haematobium infection, as well as studies for the identification of potentially pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 60 publications
0
52
0
2
Order By: Relevance
“…Infection with S. haematobium can result in a wide range of bladder pathogenesis, such as fibrosis, hyperplasia, dysplasia, squamous metaplasia, hematuria, and ultimately bladder cancer [2932]. The link between S. haematobium infection and bladder cancer is so strong that the International Agency for Research on Cancer considers urogenital schistosomiasis as a class-1 carcinogen, “carcinogenic to humans” [33].…”
Section: Discussionmentioning
confidence: 99%
“…Infection with S. haematobium can result in a wide range of bladder pathogenesis, such as fibrosis, hyperplasia, dysplasia, squamous metaplasia, hematuria, and ultimately bladder cancer [2932]. The link between S. haematobium infection and bladder cancer is so strong that the International Agency for Research on Cancer considers urogenital schistosomiasis as a class-1 carcinogen, “carcinogenic to humans” [33].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins at the interface between the host and the parasite are believed to play a key role in host immune system modulation and parasite survival [63] and so characterisation of these molecules is desirable to further our knowledge of parasite biology and pathogenesis and intervention targets. For example, the proteins secreted and located on/in the tegument of the blood-dwelling adult fluke are immune-accessible, and egg ES molecules are involved in the generation of a tumorigenic environment [13] and can be studied to gain insight into host pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, some eggs get trapped in the bladder wall causing a chronic local inflammation that will develop into a granuloma accompanied by relentless cell proliferation and ultimately in some patients, bladder cancer [16] as well as genital malignancy in women [17, 18]. The initial inflammatory response is thought to be a reaction to mechanical damage caused by passing of eggs through the urothelium (a multilayered epithelium that lines most of the urogenital tract) [13]; however, proteins secreted by parasite eggs have also been shown to increase cell proliferation and angiogenesis [13]. One of the most abundant proteins secreted by S .…”
Section: Introductionmentioning
confidence: 99%
“…3 In North Africa, however, a predominance of squamous cell carcinoma (SCC) is seen, which is caused by Schistosoma haematobium infections. 4 While the evidence linking infection by Schistosoma infection to SCC of the bladder is convincing, 5,6 the association between common urinary tract infection (UTI) and bladder cancer remains unclear. [7][8][9][10][11][12] In 1984, Kantor et al found that a history of three or more UTIs was associated with a twofold increased risk of bladder cancer overall and a nearly fivefold increased risk of SCC.…”
Section: Introductionmentioning
confidence: 99%